The Students’ Difficulties In Speaking English By The Second Semester Of English Education Study Program Of Nommensen HKBP University - Tambunan, Agnes Tiomadina; Pasaribu, Yessy Octavianna; Tampubolon, Sahlan (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This research investigates the speaking difficulties faced by second-semester students of the English Education Research Program at Nommensen HKBP University. Using a descriptive qualitative method, the research identifies the types of difficulties students encounter, the contributing factors, and the proposed solutions. Data were collected through classroom observation and interviews with 10 students. The findings indicate that the main types of speaking difficulties include inhibition, nothing to say, low or uneven participation, and the use of the mother tongue, based on Ur Penny’s framework. These issues are influenced by internal factors such as anxiety, lack of vocabulary, low self-confidence, and external factors including teaching methods and classroom environment. The analysis also reveals that students often rely on their native language due to discomfort with English. Solutions suggested include consistent practice, vocabulary enhancement, supportive teacher feedback, and promoting an English-only environment in class. This research is expected to provide useful insights for educators in designing more effective instructional strategies and improving students' communicative competence.